Dpp-induced Egfr signaling triggers postembryonic wing development in Drosophila - Paul, Litty (National Academy of Sciences, 2013)
The acquisition of flight contributed to the success of insects and winged forms are present in most orders. Key to understanding the origin of wings will be knowledge of the earliest postembryonic events promoting wing outgrowth. The Drosophila melanogaster wing is intensely studied as a model appendage, and yet little is known about the beginning of wing outgrowth. Vein (Vn) is a neuregulin-like ligand for the EGF receptor (Egfr), which is necessary for global development of the early Drosophila wing disc. vn is not expressed in the embryonic wing primordium and thus has to be induced de novo in the nascent larval wing disc. We find that Decapentaplegic (Dpp), a Bone Morphogenetic Protein (BMP) family member, provides the instructive signal for initiating vn expression. The signaling involves paracrine communication between two epithelia in the early disc. Once initiated, vn expression is amplified and maintained by autocrine signaling mediated by the E-twenty six (ETS)-factor PointedP2 (PntP2). This interplay of paracrine and autocrine signaling underlies the spatial and temporal pattern of induction of Vn/Egfr target genes and explains both body wall development and wing outgrowth. It is possible this gene regulatory network governing expression of an EGF ligand is conserved and reflects a common origin of insect wings.